ANALISIS BIAYA, PENDAPATAN, R/C DAN BAGI HASIL USAHA TANI CABAI MERAH KELOMPOK TANI BINTANG SUBUR - Septina Louisa Siahaya; Muhammad H. Takimpo (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this research is to determine the amount of production costs, revenue and R/C value of the Bintang Subur farmer group for one harvest season and analyze the profit-sharing system that has been implemented . This research was conducted on the Bintang Subur Farmers Group consisting of 9 (nine) farmers located in Telaga Pange Village .The research period starts from April 2022 – June 2022 using survey method, and analyzed further through the calculation of Total Cost (TC), Revenue (Pd) and R/C ratio .Meanwhile data reduction techniques are used for profit sharing system analysis. The total cost for red chili harvest in June 2022 is Rp. 2.670.000 with revenue value for Rp. 40,890,000 and R/C ratio of 16.3. In addition, the profit-sharing system at the Bintang Subur Farmers Group did not involve the local village head at the time of its initial establishment. The agreement is also made orally based on mutual agreement, so it does not have an element of legality in making a profit-sharing agreement.